Learning communication from erroneous video-based examples: A double-blind randomised controlled trial. Issue 6 (June 2017) - Schmitz, Felix Michael; Schnabel, Kai Philipp; Stricker, Daniel; Fischer, Martin Rudolf; Guttormsen, Sissel
Highlights: Video-based worked examples do foster initial communication skills learning. The learning effect is very strong when examples are erroneous. Self-explanation prompts and elaborated feedback should be provided too. Abstract: Objective: Appropriate training strategies are required to equip undergraduate healthcare students to benefit from communication training with simulated patients. This study examines the learning effects of different formats of video-based worked examples on initial communication skills. Methods: First-year nursing students ( N  = 36) were randomly assigned to one of two experimental groups (correct v. erroneous examples) or to the control group (no examples). All the groups were provided an identical introduction to learning materials on breaking bad news; the experimental groups also received a set of video-based worked examples. Each example was accompanied by a self-explanation prompt (considering the example's correctness) and elaborated feedback (the true explanation). Results: Participants presented with erroneous examples broke bad news to a simulated patient significantly more appropriately than students in the control group. Additionally, they tended to outperform participants who had correct examples, while participants presented with correct examples tended to outperform the control group. Conclusion: The worked example effect was successfully adapted for learning in the provider-patient communication domain. Practice Implications: Implementing video-based worked examples with self-explanation prompts and feedback can be an effective strategy to prepare students for their training with simulated patients, especially when examples are erroneous.